Interactive effects of light, nitrogen source, and carbon dioxide on energy metabolism in the diatom Thalassiosira pseudonana - Shi, Dalin; Li, Weiying; Hopkinson, Brian M; Hong, Haizheng; Li, Dongmei; Kao, Shuh-Ji; Lin, Wenfang (Supplement to: Shi, D et al. (2015): Interactive effects of light, nitrogen source, and carbon dioxide on energy metabolism in the diatom Thalassiosira pseudonana. Limnology and Oceanography, 60(5), 1805-1822, https://doi.org/10.1002/lno.10134, 2015)
Due to the ongoing effects of climate change, phytoplankton are likely to experience enhanced irradiance, more reduced nitrogen, and increased water acidity in the future ocean. Here, we used Thalassiosira pseudonana as a model organism to examine how phytoplankton adjust energy production and expenditure to cope with these multiple, interrelated environmental factors. Following acclimation to a matrix of irradiance, nitrogen source, and CO2 levels, the diatom's energy production and expenditures were quantified and incorporated into an energetic budget to predict how photosynthesis was affected by growth conditions. Increased light intensity and a shift from inline image to inline image led to increased energy generation, through higher rates of light capture at high light and greater investment in photosynthetic proteins when grown on inline image. Secondary energetic expenditures were adjusted modestly at different culture conditions, except that inline image utilization was systematically reduced by increasing pCO2. The subsequent changes in element stoichiometry, biochemical composition, and release of dissolved organic compounds may have important implications for marine biogeochemical cycles. The predicted effects of changing environmental conditions on photosynthesis, made using an energetic budget, were in good agreement with observations at low light, when energy is clearly limiting, but the energetic budget over-predicts the response to inline image at high light, which might be due to relief of energetic limitations and/or increased percentage of inactive photosystem II at high light. Taken together, our study demonstrates that energetic budgets offered significant insight into the response of phytoplankton energy metabolism to the changing environment and did a reasonable job predicting them.
Keywords: Biomass/Abundance/Elemental composition; Bottles or small containers/Aquaria (<20 L); Chromista; Gene expression (incl. proteomics); Growth/Morphology; Laboratory experiment; Laboratory strains; Light; Macro-nutrients; North Pacific; Ochrophyta; Other metabolic rates; Pelagos; Phytoplankton; Primary production/Photosynthesis; Single species; Thalassiosira pseudonana